STUDI EKSPERIMENTAL KUAT LENTUR BAJA PROFIL I KOMPAK SIMETRIS GANDA BERDASARKAN RSNI 03-1729.1-201X - , Dicki Dian Purnama ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The danger of buckling and instability structures easily occurs on the steel beam structure, it will make the structure fails before it reaches the cross section ultimate capacity.In that case the strength of a beam is not only determined by cross-section ultimate capacity. The instability of the structure causes lateral torsional buckling eventhough there is no torque on the beam. There is one way to support the stability of the beam